Causes and consequences of disordered hyperuniformity in global drylands - Wensi Hu; Lijuan Cui; Manuel Delgado-Baquerizo; Ricard Solé; Sonia Kéfi; Miguel Berdugo; Nuo Xu; Bo Wang; Quan-Xing Liu; Chi Xu (Proceedings of the National Academy of Sciences, 2025)
Self-organization of individual organisms at a very small scale may result in recognizable functional ecosystem structures at a larger spatial scale. Drylands, which cover almost half of emerged lands, host some of the most remarkable vegetation patterns on Earth, including “disordered hyperuniformity,” a recently defined class of such emergent self-organization structures. Yet, the extent, causes, and consequences of disordered hyperuniform vegetation patterns in drylands remain virtually unknown. Here, we analyzed high-resolution remote sensing images of 425 spot-like drylands across the globe and found that disordered hyperuniformity shapes vegetation patterns in about one out of ten drylands, with the distribution of plants appearing to be “disordered” to the naked eye, but supporting highly recognizable (uniform) patterns at larger scales ( ca. 50 to 500 m). Using mathematical models, we identify three potential mechanisms that can generate disordered hyperuniform vegetation patterns. These mechanisms are not limited to the well-studied Turing patterns and represent key general processes with respect to plant–plant or plant–sediment interactions. Further modeling indicates that disordered hyperuniformity enhances ecosystem functioning in terms of water retention use, and expands the range of aridity conditions under which the system can maintain itself, but may slow recovery of vegetation structure from disturbances. In a wider context, we also show that disordered hyperuniformity is likely to pertain to diverse dryland systems, such as termite-mound or fairy-circle landscapes. Our findings highlight that exploring disordered hyperuniformity of vegetation pattern of drylands (and potentially other large-scale systems) offers insights into the organization and resilience of ecosystems globally.